Novel ZnFe2O4 decorated on ZnO nanorod: Synergistic photocatalytic degradation of tetracycline, kinetics, degradation pathway and antifungal activity. Issue 3 (June 2022) - Akshhayya, C.; Okla, Mohammad K.; Al-Qahtani, Wahidah H.; Raaja Rajeshwari, M.; Mohebaldin, Asmaa; Alwasel, Yasmeen A.; Soufan, Walid; Abdel-Maksoud, Mostafa A.; AbdElgawad, Hamada; Raju, Lija L.; Thomas, Ajith M.; Sudheer Khan, S.
Abstract: In this work, ZnFe2 O4 was coupled with ZnO nanorods for the development of ZnO/ZnFe2 O4 heterojunction. The particles were synthesized via a simple co-precipitation assisted solvothermal method. The existence of elements, morphology, structure and the nature of the prepared nanomaterials were characterized using several characterization techniques such as SEM, TEM, EDAX, XPS, FTIR, XRD, Raman, UV–vis DRS, PL, EIS and ESR. The catalyst containing 60% doped ZnFe2 O4 showed the best performance amongst others (20% and 40%) and the controls. ZnO/ZnFe2 O4 -60 showed 94% degradation efficiency against tetracycline in 240 min under visible light with a rate constant of 0.011 min −1 . The mechanism of degradation was explained using the results obtained from the scavenging experiments. The TOC analysis confirmed the complete mineralization of the TC by the NCs. The intermediate compound formed was identified and the degradation pathway was elucidated by GC-MS analysis and the plausible pathway was further confirmed according to the values obtained from the Fukui function. The reusability and stability studies reveal the high photo-stable nature of the prepared NCs. Thus, this current work can be considered as a potential candidate for effective the removal of toxic pollutants from wastewater. Graphical Abstract: ga1 Highlights: ZnFe2 O4 decorated on ZnO nanorods was prepared via co-precipitation assisted solvothermal method. Superior photocatalytic degradation of TC was exhibited by ZnO/ZnFe2 O4 -60%. Hydroxyl radical are the major species involved in the photodegradation process. Excellent reusability and structural stability were shown by the NC. The NCs possessed anti-fungal activity.